Knowledge, attitude, and willingness to pay for Malayan Tapir conservation among wildlife center visitors in Selangor, Malaysia - Manikam, Sashikala; Matthew, Nitanan Koshy; Puan, Chong Leong; Ravinthra Nath, Pavithran; Ahmad, Mohd Adli (SAGE Publications Inc., 2026)
The Malayan Tapir is classified as endangered globally, with threats in Malaysia including forest loss and fragmentation, human-tapir conflicts, and roadkill incidents. The objectives of this study were to determine the knowledge and attitudes of visitors to ex-situ conservation facilities toward the Malayan Tapir and its conservation in Malaysia, to identify the factors influencing visitors’ willingness to pay (WTP) for tapir conservation, and to estimate the WTP among the visitors for the conservation of the Malayan Tapir. Data was collected through a face-to-face survey questionnaire developed using the Single Bound Contingent Valuation Method (SBCVM). A total of 358 respondents were selected using convenience sampling. The results of logit regression analysis indicated that bid, age, and attitude had significant relationship with WTP. The study found that the mean WTP for Malayan Tapir conservation fee was MYR (Malaysian Ringgit) 8.30/USD 2 per person, applicable once per visit annually. The findings will help the Malayan Tapir Conservation Action Plan committee and policymakers in formulating conservation strategies. A conservation fee could be added to the Sungai Dusun Wildlife Conservation Center.